2020
DOI: 10.1111/and.13939
|View full text |Cite
|
Sign up to set email alerts
|

Platelet indices and varicocele: A systematic review and meta‐analysis

Abstract: The updated systematic review and meta-analysis was conducted to assess the platelet indices between patients with varicocele and healthy subject. The main purpose of our study was to explore the relationship between platelet and the pathogenesis of varicocele. Databases including Cochrane Library, PubMed, and MEDLINE were retrieved to identify studies. Two independent investigators extracted the related How to cite this article:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…In our study, the mean PCT and PDW were significantly higher in the studied varicocele grades II and III compared to grade I in varicocele group associated with abnormal semen parameters. Zhang et al [11] , however, found no significant differences between patients with varicocele and those without varicocele regarding the level of PDW. Also, comparison of PDW between patients with varicocele and those without varicocele has showed no significant difference in a recent Turkish study [12] .…”
Section: Discussionmentioning
confidence: 91%
“…In our study, the mean PCT and PDW were significantly higher in the studied varicocele grades II and III compared to grade I in varicocele group associated with abnormal semen parameters. Zhang et al [11] , however, found no significant differences between patients with varicocele and those without varicocele regarding the level of PDW. Also, comparison of PDW between patients with varicocele and those without varicocele has showed no significant difference in a recent Turkish study [12] .…”
Section: Discussionmentioning
confidence: 91%